The trouble with state and local government employee pension plans: The case of Connecticut - Mark J. Warshawsky (American Enterprise Institute (AEI), 2021)
This paper reviews the literature on the recent benefit and funding landscape of state and local government employee pension plans. Many plans, with generous benefit structures and inadequate funding, are in troubled financial shape. The state of Connecticut pension plans are a good illustration of this situation. I simulate the funded ratios and actuarially determined contributions for these plans in 2030 under historical investment returns, and show the substantial risk they represent to taxpayers. I then consider policy implications which include federal mandatory funding policy and closing the plans to new workers to cap that risk.
Keywords: A; 330; Connecticut; Pensions; Public Employee Pensions; Public Pensions; Retirement